Ruled Surfaces as Pseudospherical Congruences - Gorkavyy, V. O.; Nevmerzhitska, O. M. (Журнал математичної фізики, аналізу, геометрії, 2009)
Two-dimensional ruled surfaces in the spaces of constant curvature Rn, Sn, Hn and in the Riemannian products Sn × R1, Hn × R1 are considered. A ruled surface is proved to represent a pseudospherical congruence if and only if it is either an intrinsically flat surface in Sn, or an intrinsically flat surface with constant extrinsic curvature in Sn × R1.Mathematics Subject Classification: 53B25, 53A07.